Magnetic and pH sensitive nanocomposite microspheres for controlled temozolomide delivery in glioblastoma cells - Meysam Ahmadi; Muhammad Hossein Ashoub; Kamran Heydaryan; Sanaz Abolghasemi; Elmuez A. Dawi; Ghazal khajouei; Mahnaz Amiri (Scientific Reports)
Abstract Controlled drug delivery systems have been intensively researched for cancer treatment to increase precision targeting and therapeutic efficacy. In this context, novel magnetic-/pH-sensitive graphene oxide/chitosan/iron oxide magnetic nanocomposite microspheres were synthesized. Fe3O4 (IO) nanoparticles (NPs) were synthesized via the green synthesis method in the presence of Salvia officinalis extract. The graphene oxide (GO) NPs were prepared using the Staudenmaier method, and synthesized materials were characterized. Chitosan (CS) was used to prepare microspheres. GO/CS/IO microspheres were investigated as prospective vehicles for controlled temozolomide delivery in the presence and absence of an external magnetic field. The release percentage of temozolomide molecules in the presence of 100 Hz reached a maximum in 90 min. This is approximately twice the amount of drug release in the absence of a magnetic field and more than that in the presence of a 50 Hz magnetic field. Also, the highest degree of swelling was observed at a pH of 4.5, higher than at a pH of 7.4. Also, the MTT assay results indicated the cytotoxicity of the synthesized microspheres for glioblastoma cells; notably, a significant difference was observed between the groups exposed to the magnetic field and those not, with exposure to the magnetic field further reducing survival. These results indicated that the magnetic microspheres potentially apply to controlled drug delivery systems.